2012
DOI: 10.3390/ijms131115241
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis Method for Thiosulfonate and Report of Its Insecticidal Activity in Anagasta kuehniella (Lepidoptera: Pyralidae)

Abstract: Insect pests have caused economic losses valued at billions of dollars in agricultural production. Anagasta kuehniella (Zeller), the Mediterranean flour moth, is of major economic importance as a flour and grain feeder and is often a severe pest in flourmills. This study provides a suitable route for the direct preparation of thiosulfonates 2 and 3 from thiols, under mild conditions, with good yields; these thiosulfonates were tested for their regulatory effect on insect growth. The chronic ingestion of thiosu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…[38][39][40] Studies performed by Wang and coworkers (2001) showed that diaryl disulfide (1) and the thiosulfonate (4) were cytotoxicity against human leukemia RPMI 8402 cells, stimulating DNA scission mediated by type II topoisomerase (TOP2) via S-thiolation. [26] In our results, such compounds were weakly cytotoxic (GI 50 > 50 μM) in comparison to compounds 3 and 6 whatever the cell lines were tested. As DOXO is strongly cytotoxic for all cell lines, it is not probable that the mechanism of action of all prepared compounds is resulting from TOPO II inhibition, as it happens for DOXO.…”
Section: Antiproliferative Activitiesmentioning
confidence: 46%
See 2 more Smart Citations
“…[38][39][40] Studies performed by Wang and coworkers (2001) showed that diaryl disulfide (1) and the thiosulfonate (4) were cytotoxicity against human leukemia RPMI 8402 cells, stimulating DNA scission mediated by type II topoisomerase (TOP2) via S-thiolation. [26] In our results, such compounds were weakly cytotoxic (GI 50 > 50 μM) in comparison to compounds 3 and 6 whatever the cell lines were tested. As DOXO is strongly cytotoxic for all cell lines, it is not probable that the mechanism of action of all prepared compounds is resulting from TOPO II inhibition, as it happens for DOXO.…”
Section: Antiproliferative Activitiesmentioning
confidence: 46%
“…The diaryl sulfides (1-3) were synthesized in good yields through a methodology adapted from Santos and coworkers. [26] Heating the reaction mixtures under reflux led to formation of thermodynamic controlled disulfides as the major products. IR, 1 H-NMR, 13 C-NMR and HR-ESI-MS spectra of the synthesized compounds (1)(2)(3)(4)(5)(6) are available in the Supporting Information.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that synthetic esters of thiosulfonic acids exhibit a wide range of biological activity that often exceeds the efficiency of natural analogs. Some of these esters are proposed as effective antifungal compounds [4,5], promising substances for other applications [6][7][8][9][10][11][12], preservatives of fruits and vegetables, effective plant protection products, growth regulators, biocidal additives [7,[13][14][15], insecticides, and radioprotectors [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…They are effective thiolating and sulfonylating reagents, and it is also possible to use them to stabilize polymers and creatine kinase [7,8]. Thiosulfonic esters have been proposed as effective plant protection products, growth regulators [9], biocidal additives, fruit and vegetable preservatives [10], insecticides [11], radioprotective agents and medicinal substances [12,13,14]. Therefore, it is relevant to obtain new thiosulfoesters based on γcrotonolactone.…”
Section: Introductionmentioning
confidence: 99%